The Rhetorical Model of Indonesian Research Article Introductions (RAIs) in the Law Discipline: Problems and Opportunities - Warsidi, Warsidi (Universitas Sanata Dharma, 2024)
The issue of internationalizing academic works into English Scopus-indexed journals has been becoming a growing concern in Indonesia in the last few years. However, investigating rhetorical models of local research articles is still very limited in the Indonesian context to date, while finding this foundation that underpins the global issue may overcome and create awareness for Indonesian academics for the likelihood of publishing their academic papers into reputable journals. This paper attempted to investigate the rhetorical model of Indonesian Law RAIs because none has investigated it in this selected discipline. The purpose is to discover whether or not it is different from earlier findings in English and Indonesian models. The data in the present study are 15 Indonesian Law RAIs published in accredited Science and Technology Index journals (SINTA 2). For the analysis, the study employed a genre-based study using two rhetorical models as primary code analysis. The results revealed that the Indonesian Law RAIs in the present study have a different rhetorical model from the English model, the CARS model. The main difference is the ways of establishing a niche. This finding implies that it may become an obstacle for Indonesian authors in this discipline, on the one hand, but may become an opportunity for them to publish their academic works in reputable journals, on the other hand.